The Influence of Effective Principal’s Leadership and the Availability of Infrastructure on the Successful Implementation of Distance Learning - Niar, Rika Ismah; Ahyani, Nur; Effendi, Darwin (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine: (1) the influence of the effectiveness of the principal’s leadership on the successful implementation of distance learning, (2) the effect of the availability of facilities and infrastructure on the successful implementation of distance learning, and (3) the effect of the effectiveness of the leadership of the principal and infrastructure together with the implementation of distance learning. This research was conducted at SMK Negeri 1 Prabumulih with a total of 80 teachers as respondents. This research was quantitative correlation and descriptive methods, while the sampling was done by random sampling, the research instrument uses a questionnaire. Validity test using construct validity and empirical validity. While the reliability test uses Cronbach’s Alpha. Analysis prerequisite test using normality, homogeneity, and linearity test. Data were analyzed using simple linear regression techniques, multiple linear regression and t-test. The results of the study show that (1) there is an effect of the effectiveness of the principal’s leadership on the successful implementation of distance learning, (2) there is an effect of the availability of facilities and infrastructure on the success of the implementation of distance learning, and (3) there is an influence of the effectiveness of the leadership of the principal and infrastructure as a whole. together on the implementation of distance learning.